(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
It is not recommended to open grape bushes too late, as this leads to molding of the vines and dampening off of the buds. No less dangerous is the very early opening of grapes. In this case, the bushes may be damaged by late spring frosts. Grapevines at this time are characterized by reduced frost resistance. In addition, the eyes on the vine awaken very quickly and easily die from low temperatures.